New data about the distribution of Ascopus Marshall in West Africa, with description of two new species (Coleoptera; Curculionidae; Entiminae; Cneorhinini) - Borovec, Roman; Perrin, Hélène (Zootaxa, 2023)
Ascopus longisetosus Borovec & Perrin sp. nov. from Guinea and A. suturatus Borovec & Perrin sp. nov. from Guinea and Liberia are described and illustrated. New faunistic records are presented for the species Ascopus curvipes (Hustache, 1931) (new record for Liberia), A. girardi Borovec & Perrin, 2019 (new record for Liberia, Ivory Coast and Sierra Leone), and A. pyriformis Marshall, 1951 (new record for Sierra Leone).